Coordinated Control Of A Back-ToBack HVDC Link - Latip, Ramlan (UTeM, 2016)
This thesis will present the mathematical model, controller design, simulation, and analysis of a complete back-to-back VSC HVDC system. There will be two stations of Voltage Source Converter (VSC) located back-to-back. One station shall act as a rectifier and another one will be the inverter. This will allow power transfer from one station (rectifier) to other (inverter) through a DC link. A back-to-back VSC HVDC has the advantages compare to the AC transmission because it can allow power transfer without having to synchronize both of the station or networks. In order to complete a back-to-back VSC HVDC system, it will require a d-q current controller, DC voltage controller, active/reactive power controller and DC power (DC current controller). A simulation and analysis shall be executed for each of the controller and response of voltage and current for a complete system. The simulation result will show the dynamic control of the rectifier and inverter is achieved with fast response.